Quality measurement for soft tissue sarcomas in Germany: first results of the certified sarcoma centres: research article - Rückher, Johannes; Grießhammer, Ellen; Langer, Thomas; Wenzel, Gregor; Utzig, Martin; Hohenberger, Peter; Lindner, Lars H.; Jakob, Jens; Wesselmann, Simone (Oncology research and treatment, 2023)
Introduction: Soft tissue sarcomas (STSs) are rare diseases. A high level of standardization and centralization was lacking in Germany until 2018. Methods: By developing an evidence-based guideline and a certification system for sarcoma centres, foundations for structured, guideline-based, and centralized sarcoma care were defined. First results of the certified sarcoma centres are presented. Results: The first 3 years of data collection show good results for case volume, presentation rates in pretherapeutic and postoperative tumour boards, psycho-oncological counselling, and study rates. However, other indicators (e.g., preoperative or postoperative radiotherapy for operated high-risk STS without GIST, counselling rates social services) still have potential for improvement. Based on these results, the set of indicators could be further improved. Conclusions: A sarcoma-specific quality assurance scheme that includes guideline-derived quality indicators was developed. In future, a broader database will allow further insights into sarcoma care in Germany.
Online veröffentlicht: 31. März 2023
Gesehen am 29.07.2024